Robohead: An educational Robot for Deep Robot-Student Interaction - Kolesnikov, Pavel; Klimov, Konstantin; Danilov, Vladimir; Kapytov, Dmitry (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
This paper presents an educational robot called Robohead, it is designed for a wide range of students: from elementary school to senior university courses. Robohead allows you to study the multi-machine interaction of ROS, computer vision, speech recognition and speech generation, base algorithms of control joints, touch gestures and AI integration. The paper demonstrates the architecture of Robohead and the experience of its use in educational and competitive activities.